CD19+CD24hiCD38hi B Cell Dysfunction in Primary Biliary Cholangitis - Qubo Chen; Lanmin Lai; Xiaoling Chi; Xinyi Lu; Huaxian Wu; Jing Sun; Weilin Wu; Li Cai; Xuan Zeng; Chuyang Wang; WeiCheng Chen; Anping Peng (Hindawi Limited, 2020)
CD19+CD24hiCD38hi B cells are immature transitional B cells that, in normal individuals, exert suppressive effects by IL-10 production but are quantitatively altered and/or functionally impaired in individuals with various autoimmune diseases. Primary biliary cholangitis (PBC), an autoimmune disease, clinically presents as chronic cholestasis and nonsuppurative destructive cholangitis. A role for CD19+CD24hiCD38hi B cells in PBC is unknown. This study investigated the frequency and functional variation of circulating CD19+CD24hiCD38hi B cells in PBC patients. Flow cytometry was employed to quantify the percentage of CD19+CD24hiCD38hi B cells in peripheral blood samples. Correlations between CD19+CD24hiCD38hi B cells and routine laboratory parameters were assessed. Levels of IL-10, TNF-α, IL-6 and IL-12, and Tim-1 in CD19+CD24hiCD38hi B cells from PBC patients were analyzed. The effect of CD19+CD24hiCD38hi B cells on CD4+T cell differentiation was evaluated. The percentage of CD19+CD24hiCD38hi B cells in PBC patients was significantly higher than in healthy controls and was positively correlated with liver cholestasis. After activation by anti-B cell receptor and CpG, the production of IL-10 was decreased and the production of IL-6 and IL-12 was increased in CD19+CD24hiCD38hi B cells from PBC patients. Moreover, Tim-1 levels were significantly downregulated in CD19+CD24hiCD38hi B cells from PBC patients. Coculture showed that PBC-derived CD19+CD24hiCD38hi B cells were less capable of CD4+T cell inhibition, but promoted Th1 cell differentiation. In conclusion, PBC patients have expanded percentages, but impaired CD19+CD24hiCD38hi B cells, which correlate with disease damage. In PBC patients, this B cell subset has a skewed proinflammatory cytokine profile and a decreased capacity to suppress immune function, which may contribute to the pathogenesis of PBC.